The Chaotic Property of BTA Deep-Hole Machining System under the Effect of Inner Cutting Fluid - Quanbin Zhang; Wu Zhao; Yamin Li; Shuangxi Jing (Shock and Vibration)
To clarify the action mechanism of parameter change on system stability, the chaotic property of BTA deep-hole machining system under the effect of inner cutting fluid was analyzed. According to the kinematic characteristics of the internal cutting fluid and the equation of the moment of momentum of the system, the kinematic equation of the boring bar considering the effect of the internal fluid was established. The critical conditions of chaos were deduced according to the Hamiltonian function and Melnikov function of the plane near-Hamilton system. The mechanism of the liquid filling ratio, cutting fluid flow velocity, and frequency ratio parameters on the system’s critical instability surface is investigated. The correlation and sensitivity of influencing factors, such as filling ratio and frequency ratio, and cutting fluid flow velocity to the sensitivity of system chaos are explored. The results show that in precision machining, the change of liquid filling ratio is positively related to the stability of the system, the change of cutting fluid flow velocity is negatively correlated with the stability of the system, and the change of frequency ratio has no monotonicity effect on the stability of the system. The sensitivity of the chaotic characteristics of the system to each parameter is bounded by the filling liquid ratio h = 0.58. When 0 ≤ h ≤ 0.58, frequency ratio ω¯ > filling ratio h > cutting fluid flow velocity V0; when 0.58 < h ≤ 1, filling ratio h > frequency ratio ω¯ > cutting fluid flow velocity V0. These research conclusions can lay a certain theoretical foundation for the analysis, control, and optimization of the complex mechanical behavior of BTA deep-hole machining systems in engineering practice.